Analysis Of Human Resource Competencies On The Quality Of Financial Statements In The Perspective Of Islamic Accounting - siallagan, Yuni tirtasari (ITB AAS INDONESIA Surakarta, 2024)
Financial reports are a form of accountability for the management of state / regional finances during a period and the quality of financial reports is strongly influenced by human resources. This study aims to analyze the effect of Human Resource Competence on the Quality of Financial Statements at the Office of the Pematangsiantar Human Resources Staffing and Development Agency. The research method used in this research is descriptive method with qualitative and quantitative approaches. By using a questionnaire as an instrument, the respondents in this study were financial sector employees. In this study, the sampling technique was carried out by purposive sampling and the analysis technique used was simple regression analysis, and the coefficient of determination (R2). The results showed that human resource competence has a positive and significant effect on the quality of financial reports of the Office of the Human Resources Staffing and Development Agency. In sharia accounting, the implementation of accountability must be carried out based on applicable guidelines such as the application of administration in accordance with Islamic law.